The Mouton world atlas of variation in English - Kortmann, Bernd, 1960-; Lunkenheimer, Kerstin (De Gruyter Mouton, 2012)
The Mouton World Atlas of Variation in English (WAVE) presents grammatical variation in spontaneous spoken English, mapping 235 features in 48 varieties of English (traditional dialects, high-contact mother tongue Englishes, and indiginized second-language Englishes) and 26 English-based Pidgins and Creoles in eight Anglophone world regions (Africa, Asia, Australia, British Isles, the Caribbean, North America, the Pacific, and the South Atlantic). The analyses of the 74 varieties are based on descriptive materials, naturalistic corpus data, and native speaker knowledge.